Metoprolol tartrate. Сlinical use - A. A. Zateischikova (Медицинский совет, 2015)
It's hard to imagine cardiology which would not make use of beta-blockers. The medical arsenal contains a myriad of products which differ from each other by their pharmacodynamic and pharmacokinetic properties. The clinical use of beta-blockers - antagonists of catecholamines - is based on their ability to inhibit the chronotropic, inotropic and vasoconstrictor effects of catecholamines.